Development of FlippingBook-Based E-Modules Integrated with Islamic Values to Enhance Interest and Learning Outcomes - Hasrah, Hasrah; Wiratman, Arwan; Kaharuddin, Miliyani (Educational Journal of Learning Technology, 2025)
This study aims to develop FlippingBook-based e-modules integrated with Islamic values to enhance the interest and learning outcomes of Grade IX students. Using the ADDIE development model within a Research and Development (R&D) approach, the module was tested on 30 students. Validation results showed high feasibility (media: 96%, material: 94%, language: 90%). Practicality tests from teachers and students both reached 92% (very practical). Effectiveness was confirmed by an average N-Gain of 0.8 (very high). The findings indicate that the e-module is valid, practical, and effective for learning Islamic Religious Education and Ethics.